The Meaning and Function of Mosque Ornamentation in Guci Rumpong: A Study of Aesthetics and Cultural Islamic Symbolism in Aceh - Sari, Diana; Izzati, Fuziana; Br Sembiring, Sartika (Surau Journal of Islamic Studies, 2026)
The existence of ornaments in traditional Acehnese mosques is often viewed merely as decorative elements, yet they hold the potential for deeper meanings and functions. This study aims to examine the meaning and function of the ornamentation in the Guci Rumpong Mosque in Aceh, focusing on the integration of Islamic values and local wisdom. Using a descriptive-interpretive qualitative approach, data were collected through observation and document study, then analyzed semiotically to reveal layers of symbolic meaning. The findings reveal that traditional motifs such as Lhee Sagoe (triangle), Pucok Reubong (bamboo shoot), and Oen Ranup (betel leaf) function as complex cultural texts. These ornaments symbolically convey Islamic principles, including tauhid (monotheism), cosmic harmony, spiritual growth, and social cohesion, while also serving as a “visual curriculum” for moral and religious education. Therefore, it is concluded that traditional Acehnese mosque ornaments operate as an active synthesis of art, religion, and culture. The implication of these findings underscores the importance of preserving this architectural heritage, not only as a safeguard of cultural identity but also as a relevant medium for values education in response to modernization. This study contributes to the discourse on Nusantara Islamic architecture by positioning ornamentation as a means of knowledge transmission and reinforcement of collective identity.